Peningkatan Kesehatan Mental Anak dan Remaja Melalui Ibadah Keislaman - Lubis, Layla Takhfa; Sati, Laras; Adhinda, Naura Najla; Yulianirta, Hera; Hidayat, Bahril (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2019)
In modern situation giving positive and negative impacts to children and adolescent development, including moral development and mental health for children stage to adolescent development phase. According to the previous studies described the adolescent need self-control to think, act, attitude, based on religion value, especially in Islam perspective. To develop and improving the potential of adolescent health, especially mental health or mental hygiene. In early adolescence development phase, the mind develops into abscond, conceptual, and future-oriented. Adolescence as a formal operating stadium, shows a lot of extraordinary creativity potential that should be express in writing, music, art, poetry, and other positive or productive works. Therefore, with the great potential on adolescents phase, they need reference for improving their mental health according to Psychology and Islam through Islamic worship, so that their goals of life as students become focused. This scientific article uses library research method. The results of library research showing these children and adolescent which understanding and appreciating the implementation of worship are be able to overcoming the problems of life experienced, capable to adjust the environment, maintaining relationships with the environment and thankful to God, so they tend to have good mental health standards.